UJI DATA KONFIGURASI METODE RESISTIVITAS (KONFIGURASI WINNER, DIPOLE-DIPOLE, POLE-DIPOLE) BERDASARKAN PENGUKURAN LAPANGAN DAN UJI LABORATORIUM - Dayattullah, Muhammad; Supriyanto, Supriyanto; Lepong, Piter; Rinaldi, Aditya (GEOSAINS KUTAI BASIN, 2018)
Geoelectric Resistivity is one of the geophysical methods that utilize different electrical properties in the earth in the form of resistance type in rocks. In this research, was measurements on Kadrie Oening Street at Pulau Balang formation and measurement of laboratory scale resistivity at Electronic and Instrumentation Laboratory. From the field measurements, three configurations are used: Wenner Alpha, Dipole-Dipole and Pole-Dipole. From the three configurations, sandstone resistivity value between 11.93 W.m to 33.61 W.m, clay ranged between 3.86 W.m to 10.82 W.m, siltstone range between 4.80 W.m to 9.72 W.m, coal ranged between 83.88 W.m to 216.47 W.m. The resistivity data inversion shows that the Wenner Alpha and Dipole-Dipole configurations are more compatible with field conditions in displaying the slope of the coating than the Pole-Dipole configuration.